MEMASARKAN VISI KEPADA PEMEGANG SAHAM - Nazwirman Nazwirman (Universitas Bina Sarana Informatika, 2012)
To convince the shareholders, management companies need to create and communicate the corporatevision. The company's vision should include the concept of sustainability, because it can provide acompetitive advantage in the long run. Companies in the business landscape, particularly on thepolarization of the market and the scarcity of natural resources can add significant meaning of theconcept of sustainability. Companies need to communicate to the shareholders that the application ofsustainable business practices will enhance the implementation of sustainable business practices thatwill increase productivity costs, revenue and brand value of the company.Key words: Vision, Shareholders, Sustainability